2002
DOI: 10.1021/jf025701p
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Yellow Pigment Content and Evaluation of Carotenoids by High-Performance Liquid Chromatography in Durum Wheat Grain

Abstract: The so-called "yellow pigment" content of durum wheat has been used for a long time as an indicator of the color quality of durum wheat and pasta products. For decades the chemical nature of these pigments has been assigned to carotenoids, mainly to the xanthophyll lutein and its fatty acid esters. The chemical composition of the yellow pigments of eight German durum wheat cultivars was studied. Grains were milled on a laboratory mill. Pigment extraction of millstream fractions was performed according to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
161
5
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(193 citation statements)
references
References 5 publications
(6 reference statements)
25
161
5
2
Order By: Relevance
“…durum) is lutein (Hentschel et al 2002), which confers a natural yellow color to pasta products. This is a desirable quality trait for pasta and, therefore, an important target in durum wheat breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…durum) is lutein (Hentschel et al 2002), which confers a natural yellow color to pasta products. This is a desirable quality trait for pasta and, therefore, an important target in durum wheat breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…The final yellow color of the pasta is the result of the accumulation of a mixture of natural carotenoid pigments present in the seeds and of their oxidative degradation by lipoxygenase (Lox) activity (Troccoli et al 2000). It was also suggested that, in addition to the carotenoids, some other compounds contribute to the yellow pigments present in the durum wheat seeds (Hentschel et al 2002).…”
Section: Seed Yellow Pigmentmentioning
confidence: 99%
“…High levels of yellow pigments in pasta/tetraploid wheat are favored by durum wheat breeders due to consumer preferences. In contrast, consumers desire white flour for bread baking, and consequently hexaploid/ bread wheat (Triticum aestivum) varieties have been selected for very low levels of carotenoid (yellow) pigments (Hentschel et al, 2002). Carotenoid accumulation during wheat endosperm development was previously examined using a doubled haploid bread wheat population (Howitt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%